THE INFLUENCE OF THIRD PARTY FUNDS, NON-PERFORMING FINANCING AND PROFIT SHARING ON FINANCING DISBURSEMENT (CASE STUDY AT BANK ACEH SYARIAH) - Argun Sahli; Adnan; Darmawati Muchtar; Husaini; Rico Nur Ilham (PT. Radja Intercontinental Publishing, 2023)
This study aims to analyze the effect of third party funds, non-performing financing and profit sharing on the distribution of financing at PT. Aceh Syariah Bank. Where in this study the distribution of financing is seen from murabahah receivables + profit sharing financing + leasing financing. This study uses a quantitative method with the Autoregressive Distributed Lag (ARDL) approach. This study uses time series data or time series data where this research was conducted during the period 2017 to 2021. The results of this study indicate that third party funds in the short term have no effect on the distribution of non-performing financing in the short term, have a negative and significant effect on distribution of profit-sharing financing in the short term has a positive and significant effect on financing distribution.